Hope and despair in the Iranian society: A case study of students of universities in Tehran - K. Keshavarz (Taḥqīqāt-i Farhangī-i Īrān)
Students play a vital role in determining the future of their country, and in the case of Iran, their mental state with regard to hope and despair in planning their future has an impact on the Iranian society. For years, hope and concern about the future and the feeling of futureless Iranian society are the issues that have attracted thinkers, politicians and social activists. This article tries how to focus on the formation of hopeful or hopeless mindset of students in the prevailing constitutions in contemporary Iran. The research is qualitative in nature where interviews have been conducted with 26 female and male students from public universities in Tehran using a semi-structured questionnaire. The thematic analysis method was used for the acquired data. In this article, Ghassan Hage, a Lebanese-Australian anthropologist's conceptualization of societies as "mechanisms of production and distribution of hope" is used. The findings show that collective hope an important part is absent among research participants; they, due to the existence of systematic discrimination, are excluded from the circle of production and distribution of hope. One of the consequences of social despair among the research participants is their desire to migrate outside of Iran. Since the economic, political and social obstructions fuel the spread of social despair among the participants, the recognition of social movements and the openness of governing institutions to the economic, social and political demands of the people and efforts to fulfill these demands can help spread social hope in the community. The results of this research can deepen our view on the issue of hope among all sections of the society.